Balancing parental responsibility and state obligation in fulfilling the socio-economic rights of children under the African Charter on the Rights and Welfare of the Child - Sloth-Nielsen, Julia (University of Pretoria, 2006)
Thesis (LLM (Human Rights and Democratisation in Africa))--University of Pretoria, 2003.